The effectiveness of postpartum education and support models in enhancing mothers’ self-efficacy after cesarean section - Elin Supliyani; Ina Handayani; Novita Dewi Pramanik; Ni Wayan Suarniti (Healthcare in Low-resource Settings)
Mothering self-efficacy refers to a parent’s belief in their ability to care for a child, which can be influenced by experience, knowledge, and physical condition after giving birth by cesarean section (CS). Education and postpartum support for mothers after a CS are essential for enhancing their knowledge, skills, and confidence in caring for their babies, helping them feel more prepared and capable. This study examined the effectiveness of a postpartum education and assistance model on the mothering self-efficacy of mothers who have undergone CS. This research was conducted at Bogor City Hospital (Indonesia) using a quasi-experimental method with a non-equivalent control group design, employing pre-test and post-test assessments. The sample obtained through purposive sampling consisted of 44 post-CS mothers, with 22 in the intervention group and 22 in the control group. The Wilcoxon test was used for data analysis. Mothers’ self-efficacy in caring for babies was measured before and after education and assistance using the Perceived Maternal Parenting Self-Efficacy (PMPSE) questionnaire with a Likert scale. The results showed that the median self-efficacy of post-CS mothers before the intervention was 64.50 (range 48-79), while after education and mentoring, the median increased to 81 (range 61-93). Education and mentoring significantly influenced maternal self-efficacy in caring for infants (p<0.001). It is hoped that this education and mentoring model can be applied in health facilities, particularly hospitals, to enhance the readiness of post-CS mothers to care for their babies and strengthen their confidence.